Los sonidos del misterio: análisis de tres novelas policiales en relación con la música clásica - Anchante Arias, Jim Alexander (2024)
This article seeks to analyze one of recent orientation of Detective novel, specifically aimed at the relationship between music and mystery. For this, we will focus on the analysis of three novels published in recent decades: The Last Cantata (1998) by Philippe Delelis, The Vivaldi Enigma (2005) by Peter Harris and The Prague Violinist (2007) by Michael Crane. They depict a series of events linked to mystery, conspiracy and secret societies, involving characters representing composers such as Vivaldi, Bach, Mozart, among others. It seeks to support that the detective fiction manifests a constant reinvention based on the treatise of its themes, as well as its particular relationships with history and fiction.